DISTRIBUSI SPASIAL LOGAM BERAT Pb PADA PERAIRAN TELUK KENDARI, SULAWESI TENGGARA - Armid Armid (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2015)
Study on spatial distribution of heavy metal Pb in the coastal area of Kendari Bay has been carried out. Sampling was conducted at 8 stations along the bay. Determination of Pb concentrations was performed utilizing the Atomic Absorption Spectrophotometry (AAS). The results yielded Pb concentrations within the ranges of 0.01-0.025 ppm whereby the highest level was found at station #7 (Ferry Port) and #8 (Nusantara Port). Spatial analysis via Geographic Information System was accomplished by Inverse Distance Weight (IDW) interpolation method utilizing ArcView GIS 3.3 software for mapping 42 other stations along the Kendari Bay. The results showed that, by 50 stations in total, Pb levels was moderate in the middle part of the bay with average concentration of ~0.015 ppmKeywords : Spatial analysis, heavy metal, Pb, inverse distance weight, Kendari Bay.